"I was reaching out for help and they did not help me": Mental healthcare in the carceral state - Anna G. Preston; Alana Rosenberg; Penelope Schlesinger; Kim M. Blankenship (BMC, 2022)
Abstract Background Despite the limitations the carceral environment may impose on mental wellness, mental healthcare is increasingly becoming a carceral endeavor. Over the course of the last several decades, prisons and jails have become the de facto mental healthcare provider for thousands of incarcerated individuals. Furthermore, practices like mandated mental healthcare for supervised individuals further broaden the population experiencing mental healthcare within the criminal legal system at large. This study examines the perspectives of nine individuals who experienced mental healthcare within the carceral state, whether in prison or on parole or probation, with a special focus on how attributes of the carceral state create ideological and functional barriers to effective mental healthcare. Methods Data for the parent study of this analysis was collected via in-depth, one-on-one interviews of about one hour's length, conducted at six-month intervals over the course of 2 years. These interviews were analyzed using an iterative process of open-coding, thematic code development, and code application to participant interviews. Results The results showed a common perception of mental healthcare received within the carceral state as serving goals of the prison system, including control and punishment, rather than therapeutic goals of healing and empowerment. This often had negative implications for the quality of the treatment received, including patterns of diagnostic ambiguity, treatment that was ill-fitting to participants' needs, and treatment that was undermined by the new trauma created by the prison environment. The results also highlighted racial disparities prevalent within the carceral system. Despite the barriers created by the subjection of therapeutic practices to carceral goals, participants demonstrated resourcefulness and creativity in engaging with these treatment modalities to reap benefits where possible. Conclusions Overall, these results highlight the inappropriateness of combining therapeutic and carceral spaces, the need for greater public attention to how carceral mechanisms disadvantage vulnerable populations, and the need for a cultural reconceptualization of mental illness such that it is met not with criminal punishment but appropriate care.